Empirical results of entrepreneurs’ network: case study of Slovakia - Mura, Ladislav; Havierniková, Katarína; Machová, Renáta (Serbian Journal of Management, 2017)
The changes in economic development of different countries in recent decades are influenced by processes that have modified the ways and forms of doing business. While in the past, the emphasis was put on size of the company, currently its participation in various forms of network cooperation prevails. The following paper presents results of empirical research realized between the small and medium sized enterprises involved into entrepreneurs’ networks. Research was conducted during the period 2014 – 2015 in a frame of scientific research project VEGA 1/0381/13 and KEGA 001UCM-4/2016. The main aim of paper is to propose the basic model of network entrepreneurial cooperation in the conditions of the Slovak republic. The novelty of this paper is to mention the main steps that should be done by stakeholders, if they want to create successful network. The partial aims of this paper are: the evaluation of quantitative and qualitative conditions for networking and description of partial steps which lead to creation of network cooperation. We used selected quantitative methods (Localization coefficient with combination of BCG matrix). Qualitative conditions will be evaluated through the results of questionnaire survey, which identified the entrepreneurs’ suggestions of business for engagement into the network (by using Pearson chi-square, Kruskal Wallis and Median Tests).